Perkembangan Plasenta dan Pertumbuhan Janin pada Tikus Hamil yang Diinfeksi Porphyromonas Gingivalis Placental Development and Fetal Growth in Porphyromonas Gingivalis-Infected Pregnant Rats - Banun Kusumawardani; Yuliana MD Arina; Azham Purwandhono (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2014)
Maternal Porphyromonasgingivalis infection on periodontal tissue can result in Porphyromonasgingivalisdissemination to umbillical cord. Porphyromonas gingivalis presumably gain access to the systemic circulationvia local tissue inflammation, and may affect the placental development and the fetus itself. This study aimed toanalize the effect of periodontal infection with Porphyromonas gingivalis on placental development, and todetermine its effect on fetal growth in a pregnant rat model. Female rats were infected with live-Porphyromonasgingivalis at concentration of 2x109 cells/ml into subgingival sulcus of the maxillary first molar before and/orduring pregnancy. They were sacrified on gestational day (GD) 20. Fetuses were evaluated for weight andlength. All placentas were fixed in 10% buffered formalin, processed for paraffin embedding, and stained withhematoxylin and eosin.The histopathological analysis of placentas on GD 20 showed that trophoblast cells inlabyrinth and junctional zone had a greater density in control group than Porphyromonas gingivalis-infectedperiodontal maternal group. The nucleated-erythrocytes were found more abundant in the fetal blood vessels ofPorphyromonas gingivalis-infected periodontal maternal group than in the fetal blood vessels of control group.In conclusion, the impaired placental morphology influenced the normal function of placenta to maintain thegrowth and development of fetus. The decreased placental weightresulted in the decreased of fetal weightandlength.